2012
DOI: 10.1590/s0101-31222012000300018
|View full text |Cite
|
Sign up to set email alerts
|

Espermidina exógena atenua os efeitos do NaCl na germinação e crescimento inicial de leguminosas forrageiras

Abstract: RESUMO -Objetivou-se nesse estudo avaliar o papel atenuador da espermidina exógena sobre a germinação, vigor de sementes e crescimento de plântulas de cultivares das forrageiras alfafa, guandu e labe-labe submetidas ao estresse salino. A semeadura foi realizada em caixas de plástico tipo "gerbox" forradas com papel de filtro umedecidos com soluções salinas nas concentrações de 0, 20, 40, 60, 80 e 120 mM de NaCl contendo 0 ou 0,5 mM de espermidina. O delineamento experimental foi inteiramente casualizado em esq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…Como exemplos podem ser citados os dados obtidos para milho pipoca (MOTERLE et al, 2006), soja transgênica e convencional , leguminosas forrageiras (MELLONI et al, 2012), bem como nabiça e fedegoso (PEREIRA et al, 2014).…”
Section: Resultsunclassified
“…Como exemplos podem ser citados os dados obtidos para milho pipoca (MOTERLE et al, 2006), soja transgênica e convencional , leguminosas forrageiras (MELLONI et al, 2012), bem como nabiça e fedegoso (PEREIRA et al, 2014).…”
Section: Resultsunclassified
“…As for germination, obtained as a function of different osmotic potentials (Figure 3A), the percentage of normal seedlings decreased for the three cultivars evaluated. Significant reductions in seed germination were also observed in the study of Nunes et al (2009), , Melloni et al (2012), and Pereira et al (2014). These results prove the harmful effects of salinity stress due to its osmotic or ionic impact, impairing the absorption of water or favoring the entry of ions into the cells (Braccini et al, 1996).…”
mentioning
confidence: 54%
“…The results suggest that the toxic effects of salts caused inhibition of germination. These results have been attributed to the reduction of the amount of water absorbed by the seeds in saline medium, with reduction of the osmotic potential of the solutions (Braccini et al, 1996;Melloni et al, 2012).…”
mentioning
confidence: 99%
“…The same results in lablab and in another pigeonpea cultivar (cv. Caqui) were found by Melloni et al (2012), who verified that 0.5 mM Spd caused a significant decrease in seed germination under salt stress (20 -120 mM). However, these authors showed that at this decrease was smaller than the one observed in treatments with no Spd, indicating that salt stress could mitigate the effect of this polyamine.…”
Section: Resultsmentioning
confidence: 90%